2014
DOI: 10.1007/s12032-014-0166-6
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation, as measured by the neutrophil/lymphocyte ratio, may have differential prognostic impact before and during treatment with fluorouracil, irinotecan and bevacizumab in metastatic colorectal cancer patients

Abstract: The inflammatory index neutrophil/lymphocyte ratio (NLR) has an adverse prognostic value in patients with localized colorectal cancer (CRC). We aimed at evaluating its role in metastatic CRC (mCRC) patients treated with standard first-line chemotherapy. Among consecutive CRC patients referred to our Unit, those with metastatic disease eligible for treatment with fluorouracil, irinotecan and bevacizumab (FOLFIRI-Bev) were included in the study. NLR was routinely assessed before each treatment cycle and correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 37 publications
0
37
2
Order By: Relevance
“…Chronic stress may elicit prolonged secretion of cortisol 29, which triggers a counter‐regulatory response of white blood cells by downregulating their cortisol receptors. This downregulation, in turn, reduces the cell capacity to respond to anti‐inflammatory signals and allows cytokine‐mediated inflammatory processes to flourish 30, which have been validated as poor prognostic factors in cancers 31, 32. Married persons may also enjoy greater financial resources than those who are widowed or divorced due to gains from economies of scale.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic stress may elicit prolonged secretion of cortisol 29, which triggers a counter‐regulatory response of white blood cells by downregulating their cortisol receptors. This downregulation, in turn, reduces the cell capacity to respond to anti‐inflammatory signals and allows cytokine‐mediated inflammatory processes to flourish 30, which have been validated as poor prognostic factors in cancers 31, 32. Married persons may also enjoy greater financial resources than those who are widowed or divorced due to gains from economies of scale.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-treatment value of NLR has also shown predictive value in guiding treatment regimens: for example, Kim et al [32] reported a poor rate of pathological complete response in patients with high pre-treatment NLR, undergoing preoperative chemoradiotherapy for locally advanced rectal cancers. A high NLR may also indicate treatment resistance and poor survival in patients with primary, metastatic and advanced colorectal cancers [45,46,47]. The total number of lymph nodes retrieved during surgery depends on multiple factors and increases the likelihood of discovering nodal metastasis [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…There was no imbalance in KPS between GEM and GEMOXA group (KPS 80 or 90 in 53% and 42% of patients, respectively, chi-square p value = 0.209). Median BMI at treatment start was 23 (range [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Patients' Characteristics and Treatment Deliverymentioning
confidence: 99%
“…Systemic inflammation is a process associated with a number of pathological conditions, such as metabolic disorders [16], atherosclerosis [17], osteoporosis [18] and cancer [19][20][21][22][23]. It might be considered as a doubleedged weapon in that it represents the first line immune defense but also a source of cytokines and growth factors with potentially adverse effects.…”
Section: Introductionmentioning
confidence: 99%